Overview of the design of the ITER heating neutral beam injectors. (21st February 2017) - Hemsworth, R S; Boilson, D; Blatchford, P; Palma, M Dalla; Chitarin, G; de Esch, H P L; Geli, F; Dremel, M; Graceffa, J; Marcuzzi, D; Serianni, G; Shah, D; et al.
Abstract: The heating neutral beam injectors (HNBs) of ITER are designed to deliver 16.7 MW of 1 MeV D 0 or 0.87 MeV H 0 to the ITER plasma for up to 3600 s. They will be the most powerful neutral beam (NB) injectors ever, delivering higher energy NBs to the plasma in a tokamak for longer than any previous systems have done. The design of the HNBs is based on the acceleration and neutralisation of negative ions as the efficiency of conversion of accelerated positive ions is so low at the required energy that a realistic design is not possible, whereas the neutralisation of H − and D − remains acceptable (≈56%). The design of a long pulse negative ion based injector is inherently more complicated than that of short pulse positive ion based injectors because: negative ions are harder to create so that they can be extracted and accelerated from the ion source; electrons can be co-extracted from the ion source along with the negative ions, and their acceleration must be minimised to maintain an acceptable overall accelerator efficiency; negative ions are easily lost by collisions with the background gas in the accelerator; electrons created in the extractor and accelerator can impinge on the extraction and acceleration grids, leading to high power loads on the grids; positive ions are created in the accelerator by ionisation of the background gas by the accelerated negative ions and the positive ions are back-accelerated into the ion source creating a massive power load to the ion source; electrons that are co-accelerated with the negative ions can exit the accelerator and deposit power on various downstream beamline components. The design of the ITER HNBs is further complicated because ITER is a nuclear installation which will generate very large fluxes of neutrons and gamma rays. Consequently all the injector components have to survive in that harsh environment. Additionally the beamline components and the NB cell, where the beams are housed, will be activated and all maintenance will have to be performed remotely. This paper describes the design of the HNB injectors, but not the associated power supplies, cooling system, cryogenic system etc, or the high voltage bushing which separates the vacuum of the beamline from the high pressure SF6 of the high voltage (1 MV) transmission line, through which the power, gas and cooling water are supplied to the beam source. Also the magnetic field reduction system is not described.